2020
DOI: 10.1186/s13287-020-01958-3
|View full text |Cite
|
Sign up to set email alerts
|

TUG1 enhances high glucose-impaired endothelial progenitor cell function via miR-29c-3p/PDGF-BB/Wnt signaling

Abstract: Background Diabetes is associated with the dysfunction of endothelial progenitor cells (EPCs), characterized as impaired angiogenesis, a phenomenon thought to be involved in the development of diabetic foot. lncRNA plays an essential role in microvascular dysfunction and signaling pathways in patients with diabetes. lncRNA taurine upregulated gene 1 (TUG1) participates in angiogenesis in various cells. However, the mechanisms of TUG1 activity in EPCs have not been elucidated. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Based on the online J o u r n a l P r e -p r o o f databases, ENCORI for RNA interactomes (http://starbase.sysu.edu.cn/), predicated the potential candidates for hsa_circ_0001020. MiR-29c-3p is one of the predicated candidates for hsa_circ_0001020, and exerts an important role in regulating EPC function [21], therefore, we focused on the expression and function of miR-29c-3p in subsequent experiments. We found miR-29c-3p significantly reduced in peripheral blood from DVT patients compared with health control (Figure 3A).…”
Section: Hsa_circ_0001020 Severs As a Sponge Of Mir-29c-3pmentioning
confidence: 99%
“…Based on the online J o u r n a l P r e -p r o o f databases, ENCORI for RNA interactomes (http://starbase.sysu.edu.cn/), predicated the potential candidates for hsa_circ_0001020. MiR-29c-3p is one of the predicated candidates for hsa_circ_0001020, and exerts an important role in regulating EPC function [21], therefore, we focused on the expression and function of miR-29c-3p in subsequent experiments. We found miR-29c-3p significantly reduced in peripheral blood from DVT patients compared with health control (Figure 3A).…”
Section: Hsa_circ_0001020 Severs As a Sponge Of Mir-29c-3pmentioning
confidence: 99%
“…63 In the study by Li et al, overexpression of lncRNA taurine upregulated gene 1 (TUG1) restored the ability of migration, invasion, and tube formation in high-glucose treated EPCs. 64 In vivo, TUG1 overexpression promoted angiogenesis in a diabetic mouse ischemic limb model.…”
Section: Role In Diabetic Microvascular Injurymentioning
confidence: 99%
“…Many studies reported that TUG1 is involved in angiogenesis during the progression of various diseases 18,19 . One miRNA in particular, miR‐29c‐3p, could be directly targeted by TUG1 to stimulate angiogenesis in endothelial progenitor cells and diabetic mouse ischemic limb 20 . Besides, previous studies showed that TUG1 exerts oncogenic functions by interacting with miR‐29c‐3p in several cancers 9,21 .…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 One miRNA in particular, miR‐29c‐3p, could be directly targeted by TUG1 to stimulate angiogenesis in endothelial progenitor cells and diabetic mouse ischemic limb. 20 Besides, previous studies showed that TUG1 exerts oncogenic functions by interacting with miR‐29c‐3p in several cancers. 9 , 21 Additionally, it has been reported that miR‐29c‐3p could suppress cell proliferation and induce apoptosis in lung cancer by targeting angiogenic factor VEGFA.…”
Section: Introductionmentioning
confidence: 99%